Comparison Between Harmonic scalpel and Cold dissection in Tonsillectomy at Shree Birendra Hospital: A Retrospective Study - Karki, Reeba; Mahaseth, Rajeev Kumar; Dutta, Vijay Bhushan; Bhattarai, Sriya (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Tonsillectomy is the most common surgery performed by otorhinolaryngologist worldwide. It is a surgical procedure of removing tonsil with commonest indications for recurrent tonsillitis and tonsillar hypertrophy. The two most important complications of this surgery are bleeding (intraoperative, postoperative) and postoperative pain. Various surgical techniques have been developed to minimize this complication. Harmonic scalpel is an ultrasonically activated surgical device which can coagulate and cut vessels and tissues at a very low temperature. This study was conducted to compare the operative time, intraoperative blood loss and early post-operative pain between Harmonic scalpel and cold dissection tonsillectomy. Methods: This was a retrospective study conducted in ENT and Head and Neck Surgery department of Shree Birendra Hospital, Chhauni, Kathmandu from July 2018 to July 2019. Each patient was assessed by ENT Head and Neck Surgeon. Clinically diagnosed recurrent tonsillitis and tonsillar hypertrophy were included in the study. Those with age < 14 years, acute infection, obstructive sleep apnoea syndrome, adenoid hypertrophy, nasal pathology, cleft, history of bleeding disorders, inability to give informed consent, individual who would have difficulty communicating their pain levels, any chronic illness was excluded. Results: Out of 50 patients, 33(66%) were males and 17(34%) were females. The operative blood loss in harmonic scalpel was lesser (21.89 ± 8.89 ml) than in cold dissection group (49.74 ± 19.69 ml) which was statistically significant (p value = 0.000). The operating time in harmonic scalpel group was longer (8.48 ± 4.58 minutes) than in cold dissection group (8.14 ± 2.01 minutes). Pain on the early postoperative period (3 hours post-surgery, 1st and 2nd postoperative day) was lesser in harmonic scalpel group 68% (34/50) than in cold dissection group 32% (16/50). Conclusion: Harmonic scalpel is easy to use instrument which reduces intra-operative blood loss and post-operative pain as compared with cold dissection method.